MINERALOGICAL CHARACTERS OF KARANG PANINGAL EPITHERMAL VEIN DEPOSITS, WEST JAVA - TATANG WAHYUDI (Indonesian Mining Journal, 2011)
Karang Paningal gold-ore deposits belong to the epithermal deposits. As hydrothermal deposits, the alter- ation that occurs in this area comprises argillitization, sericitization and silicification. The gold is included within several veins that perform three texture types, namely chalcedony, comb and vuggy. Based on its mineral contents and vein deposit types, mineralization at Karang Paningal took place in two stages that was early epithermal process producing comb-vuggy vein deposit and final epithermal deposit retaining chalcedony vein deposit. Zone of prospective mineralization takes place within vein and rocks beneath and above veins